(untitled) (Quinto Sol, 2026)
In the town of San Pedro, located in the Yungas region of Jujuy, the company Aráoz, Ugarriza, Uriburu y Cía. was formed in 1882, which would found a modern sugar mill on those lands. The incorporation of the British technician, Roger Leach, led to him becoming associated with the firm in 1888, hegemonizing it by 1893, by forming Leach Hnos. This article analyzed the territorial layout of the sugar mill, as well as its strategies for almost exclusive use of water —a vital resource for sugarcane cultivation— relying on the resources of local municipal power. For this purpose, we will combine the analysis of official documentation of the province with the official statistical records on the sugarcane expansion, until the sector’s first crisis in 1895.